Long-term Growth Effects of Natural Disasters - Empirical Evidence for Droughts - Michael Berlemann; Daniela Wenzel (Center for Economic Studies and ifo Institute (CESifo), 2015)
The ongoing process of climate change goes along with a higher frequency and/or severity of droughts. While the short-term growth consequences of droughts are comparatively well examined, little research has yet been devoted to the question whether and how droughts affect medium and long-term growth. However, knowledge on the growth dynamics triggered by natural disasters is an influential input factor for integrated assessment models which are used to evaluate climate policy measures. In this paper we deliver empirical support for the hypothesis of the existence of long-run growth effects of droughts. Based on a panel of 153 countries over the period of 1960 to 2002 and employing a truly exogenous drought indicator derived from rainfall data we find significantly negative long-term growth effects of droughts in both highly and less developed countries. We also deliver first empirical evidence on the channels through which droughts affect economic growth.
Keywords: Q54; O16; H84; 330; climate change; natural disasters; droughts; economic growth; transmission channels